The Impact of the Comprehensive Ban Due to the COVID-19 on the Quality of Ambient Air in Jordan. Study for 15th March to 15th April of 2020 Period - AL-BILLEH, Tareq (Journal of Environmental Management and Tourism, 2022)
This research deals with the impact of the comprehensive ban due to the COVID-19 pandemic during the period from (15 th March 2020) until (15 th April 2020) on the quality of the surrounding air in Jordan, where it highlighted  the extent to which air quality is protected in international conventions and Jordanian legislation, and showed the role of Jordanian government measures taken to confront the Corona virus in reducing ambient pollutants in the surrounding air in Jordan, whereas the research dilemma lies in addressing the impact of government decisions during the COVID-19 pandemic period on reducing emissions and improving ambient air quality in main cities in Jordan, the research also concluded several results and recommendations, the most important of which is improving the ambient air quality that recorded in most monitoring centers in Jordanian cities as a result of the precautionary measures taken by the Jordanian government to limit the spread of the COVID-19, as the pivot of these measures was the closure of most industrial activities, the prevention of transportation between governorates, and the commitment of millions of the Kingdom's residents to their homes, which led to a decrease in the percentage of emissions resulting from vehicle exhaust, and industrial, commercial.